Synergistic effects of combinatorial Lactiplantibacillus plantarum fermentation and vegetable oils supplementation on the lycopene level, antioxidant capacities and flavor volatiles of tomato pulp. (December 2022) - Guo, Zhaoyan; Wang, Yanyao; Wang, Chengxin; Guo, Jiayu; Wang, Xin; Xu, Huaide; Lei, Hongjie
Abstract: The objective of this study was to investigate the effects of Lactiplantibacillus plantarum ( L. plantarum ) fermentation and three types of vegetable oils (corn oil, peanut oil, and olive oil) supplementations on the physicochemical properties, bioactive components, and flavor volatiles of tomato pulp. Tomato pulp supplemented with oils was excellent food matrices for L. plantarum growth, and the colony counts remained above 8.3 log CFU/mL at the end of fermentation. The contents of total phenol, carotenoids and lycopene were dramatically increased after fermentation, and oils supplementation exhibited a synergistic promotion effect, especially for the combination of L. plantarum fermentation and 3% olive oil supplementation exhibiting the highest lycopene level (30 mg/mL), the strongest DPPH radical scavenging activity (84.24%) and FRAP (16.45 mmol Trolox/L). Furthermore, synergistic L. plantarum fermentation and oils supplementation decreased aldehydes content, and increased alcohols, esters, and ketones formation, meaning the improved flavor characteristics of fermented tomato pulp. Industrial relevance: In this study, a functional beverage of tomato pulp was prepared by the combination of L. plantarum fermentation and vegetable oils supplementation. Colony counts, lycopene level, antioxidant capacities, and flavor characteristics were dramatically improved at the end of fermentation. This study provides an innovative technology to improve the release of lycopene from plant tissue and provide a functional beverage of tomato pulp with high health benefits. Graphical abstract: Unlabelled Image Highlights: Tomato pulps added with oils were good matrices for Lactiplantibacillus plantarum . Combination of L. plantarum and oil promoted lycopene release from plant tissue. Antioxidant capacity was improved by combination of L. plantarum and oil. Esters and ketones formation was increased by combination of L. plantarum and oil.